A qualitative study of emergency management considerations for big-bodied people in Aotearoa New Zealand. (January 2022) - Gray, Lesley; MacDonald, Carol; Becker, Julia S.; Johnston, David
Abstract: Due to their circumstances and resources before, during and following disaster events, some people have higher risk of harm in disaster requiring specific disaster planning considerations. The prevalence of big bodied people (BBP) is increasing in many countries and BBP are potentially at higher risk in disasters in direct relation to their size, shape and weight. This study explores planning considerations by emergency management, health, humanitarian and resource sector (EMs) for BBP in New Zealand. Qualitative semi structured interviews explore EM considerations particular to BBP. A purposive sampling recruitment technique was employed. Fifteen EM individuals were interviewed in-person or via Zoom between July 2018–April 2021 . Interviews were audio recorded and transcribed. Data were thematically analysed. Five themes were identified: Prioritising People; Overlooked and left behind; Whose job is it anyway?; Practical and resource issues; The way forward. Participants were readily able to identify a range of 'groups' likely to be at higher risk in disasters, however BBP were not identified as at-risk and no specific planning was in place. A one size approach was more likely to overlook specific needs of BBP with lack of clarity over who would be responsible for planning. While concerning that BBP were not currently included in planning, emergency managers were open to education. The EMs interviewed expressed a desire for information, education and training to build the knowledge base concerning this sector of the population.